Porgy fish teeth in Miocene mari from Mastni hrib near Skocjan, Slovenia - Mikuž, Vasja; Bartol, Miloš; Šoster, Aleš (Geologija, 2014)
The article discusses fossil porgy fish teeth found in Middle Miocene (Badenian) sandy marl from Mastni hrib near Škocjan in Dolenjska. The teeth belong to the species Pagrus cinctus (Agassiz, 1836) and represent the first find in the Krka basin. In Sediments of the Central Paratethys and the Mediterranean, the fossil remains of porgy fish are relatively common.